The Effect of Problem-Based Learning Model on Vocational Students’ Mathematical Concept Understanding in Solving Numerical Problems - Syahrani, Putri; Miatun, Asih (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
This study was motivated by observations of challenges faced by vocational school students in understanding mathematical concepts. To address this issue, a Problem-Based Learning (PBL) model that actively involved students through numerical problem-solving was implemented. The sample consisted of 44 students from two Grade X classes at a vocational high school in East Jakarta. Numerical problems in the form of descriptive questions based on the System of Linear Inequalities in Two Variables (SPtLDV) were used as post-test instruments to assess students’ mathematical concept understanding. The experimental class achieved an average post-test score categorized as high. Hypothesis testing showed that students' understanding of mathematical concepts using the PBL model was significantly better than with the conventional approach. The effect size, calculated using Cohen's d formula, was 2.12—classified as high—confirming the effectiveness of the PBL model in enhancing students' understanding of mathematical concepts through numerical problem-solving.